Implementasi Deep Learning dalam Pembelajaran Bahasa Inggris bagi Siswa Usia Dini - Lilis Lestari Wilujeng; Meme Susilowati (Civiliza Publishing, 2026)
Following the restructuring of national education policy after the termination of the Sekolah Penggerak Program in 2025, the Ministry of Primary and Secondary Education shifted its focus to improving teacher quality and school leadership through quality education for all, school revitalization, and digital and artificial intelligence–based training programs. These policies stress the need to strengthen teacher competencies to face the demands of 21st-century learning so that classroom activities become more meaningful, reflective, and contextual. In this situation, higher education institutions are expected to support capacity building for teachers in partner schools, especially in early childhood education, which still faces shortages of teachers and learning resources.TK DWP Kenongo in Jabung District, Malang Regency, is one school experiencing these challenges, particularly in applying deep learning to early childhood English instruction. This community service program was conducted as Universitas Ma Chung’s effort to improve teachers’ skills in designing, implementing, and evaluating deep learning–based instruction using three principles: mindful learning, meaningful learning, and joyful learning. The program involved focus group discussions, training, mentoring in thematic module development, and evaluation. The results show better teacher understanding of deep learning lesson design and key classroom stages, including understanding, practice, reflection, and evaluation.